Identification of Babesia bigemina infected erythrocyte surface antigens containing epitopes conserved among strains - Shompole, S.; McElwain, T.F.; Jasmer, D.P.; Hines, S.A.; Katende, J.; Musoke, A.J.; Rurangirwa, F.R.; McGuire, T.C. (Wiley, 1994)
The presence of previously uncharacterized antigens (new antigens) on the surface of intact erythrocytes infected with three strains of Babesia bigemina from Kenya and one each from Puerto Rico, Mexico, St. Croix, and Texcoco‐Mexico was demonstrated by indirect immunofluorescent antibody (IFA) reactions. These antigens were not strain specific because antibodies in bovine immune serum to either the Mexico or Kenya isolates reacted with all seven strains tested. Homologous and heterologous immune serum antibodies bound a maximum of 83% and 55%, respectively, of intact erythrocytes infected with the Kenya‐Ngong strain but not uninfected erythrocytes. Both sera caused agglutination of only infected erythrocytes. Antibodies eluted from the surface of glutaraldehyde (0.25%) fixed infected erythrocytes had IFA reaction patterns among strains similar to those of immune sera before elation. Eluted antibodies were used to determine if these antigens were protein and encoded by B. bigemina. Eluted antibodies bound seven parasite‐encoded proteins of 240, 220, 66, 62, 58, 52 and 38 kDa in an erythrocyte surfacespecific immunoprecipitation reaction of 35‐methionine labelled proteins. It was concluded that the surface of B. bigemina infected erythrocytes had parasite‐encoded proteins and that these proteins had surface exposed epitopes that were conserved among the seven strains examined which were from two continents.